Negotiating family responsibilities - Finch, Janet; Mason, Jennifer (London Routledge, 1993)
Negotiating Family Responsibilities provides a major new insight into contemporary family life, particularly kin relationships outside the nuclear family. While many people believe that the real meaning of 'family' has shrunk to the nuclear family household, there is considerable evidence to suggest that relationships with the wider kin group remain an important part of most people's lives.